European guideline for the management of pediculosis pubis. (16th July 2017) - Salavastru, C.M.; Chosidow, O.; Janier, M.; Tiplica, G.S.
Abstract: Pediculosis pubis is caused by Phthirus pubis. The disease can be sexually transmitted. Patients main complain is of itch in the pubic area. The parasite can be spotted with the naked eye and blue macules can be observed in the pubic area. First line therapy consists of permethrin or pyrethrins with piperonyl butoxide. Second line therapy contains phenothrin, malathion and oral ivermectin. Partner management needs a look‐back period of time of 3 months. Pubic lice incidence is increased in populations groups living in crowded spaces with scarce sanitary conditions as in time of war or disaster.